Freelancer - Salahat, Roa'a; Joudeh, Ruba (My University, 2019)
Create a website for self-employment, through the use of wordpress, where the site is an intermediary between companies and researchers at work where any company can advertise jobs and get experts easier and faster, The job seeker also creates an account, writing the CV or logging in via LinkedIn It enables him to submit the application to the job and gets an acceptance or rejection response, and he can also evaluate the company after working with it
Keywords: web, sit ,to ,freelancer.